BCA CUSTOMER SATISFACTION ANALYSIS OF BANKING AUTOMATION SERVICES (CASE STUDY OF BUSINESS ADMINISTRATION STUDENTS UNIKA ATMA JAYA CLASS OF 2017) - Putri Aulia; Lamtiur H Tampubolon (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
Customer satisfaction is important in shaping the quality of service in a company, one of which is in the banking world, especially BCA. Without satisfaction, you will not have loyal customers. Satisfaction also contributes significantly to improving the maximum service quality. The purpose of this study was to determine the satisfaction of BCA bank customers with banking automation services, in the era of technological disruption, for students of the Atma Jaya Indonesian Catholic University Business Administration Study Program Class 2017. The type of research used was descriptive research using qualitative methods with data collection techniques. in-depth interviews to 3 key informants and 3 triangulation informants. The results of this study are the three key informants are satisfied with the BCA automation service, based on 5 indicators of customer satisfaction from Kotler & Keller.